E-Church as a Virtual Service Communities During COVID-19 Pandemics - Kartika Singarimbun (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2021)
COVID-19 threatens the survival of many people. The imposition of social isolation, social distancing, and lockdown policies, shuts down face-to-face worship at the church. Despite the stuttering information technology, the Protestant churches gradually broadcast the worship Livestream Youtube and save the video afterward; so that the congregation can watch the e-church further. The adoption of communication technology has become a new strategy for church institutions during the pandemic; by creating channels for congregations. With the theory of mediatization of religion,  media used to delivering religious content, and as Protestant virtual communities, environment to gather and participate in real-time Sunday worship on youtube Livestream. E-church is the main target of Indonesian church institutions today, although it cannot be denied that many communication aspects are missing; such as touch, emotion, and expression. By using the Indonesian Christian Church known as GKI Taman Cibunut Bandung as a case study, multi-sources of informants who were interviewed semi-structured were conducted so that the data were obtained comprehensively.